2016
DOI: 10.1227/neu.0000000000001264
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Valproic Acid on Blood-Brain Barrier Disruption and Apoptosis-Related Early Brain Injury in Rats Subjected to Subarachnoid Hemorrhage Are Modulated by Heat Shock Protein 70/Matrix Metalloproteinases and Heat Shock Protein 70/AKT Pathways

Abstract: BBB, blood-brain barrierEBI, early brain injuryHSP, heat shock proteinMMP, matrix metalloproteinasePBS, phosphate-buffered salineSAH, subarachnoid hemorrhageTUNEL, terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick-end labelingVPA, valproic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Consistent with this data, brain levels of HSP-70 were elevated after exposure to ZnONPs for 7 days as a consequence of the triggered oxidative stress and inflammation. In addition, it is demonstrated that HSP-70 is an inhibitor of apoptosis via inactivating caspase-3, and therefore could be cytoprotective [ 79 , 80 , 81 ]. The anti-apoptotic properties of HSP-70 have been attributed to its anti-oxidative action [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this data, brain levels of HSP-70 were elevated after exposure to ZnONPs for 7 days as a consequence of the triggered oxidative stress and inflammation. In addition, it is demonstrated that HSP-70 is an inhibitor of apoptosis via inactivating caspase-3, and therefore could be cytoprotective [ 79 , 80 , 81 ]. The anti-apoptotic properties of HSP-70 have been attributed to its anti-oxidative action [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sections were incubated overnight at 4°C with primary antibodies, including antibodies against NeuN (Abcam, ab177487 or ab104224) and LC3 (Cell Signaling Technology, CST#4108) followed by the appropriate fluorophore-conjugated secondary antibodies (Jackson ImmunoResearch, West Grove, PA, USA). TUNEL staining was performed according to the protocol from the manufacturer (Roche Inc., Switzerland) as described in previous studies (Ying et al, 2016 ). The sections were visualized with a fluorescence microscope (LSM-710; Zeiss, Oberkochen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Propidium iodide (PI; sigma) was dissolved in 0.9% NaCl, and 10 mg/kg PI was administered intraperitoneally at 1 h prior to sacrifice. Brain coronal slices were obtained according to our previous protocol [ 23 ]. The slices were incubated at 4 °C over night with mouse monoclonal anti-neuronal nuclei (NeuN) (1:200, MAB377, Millipore), goat polyclonal anti-caspase-1 (1:200, sc-22165, Santa Cruz), and rabbit monoclonal anti-LC3 (1:200, 3868#, Cell signaling Technology) followed by incubation with appropriate secondary antibody (1:200, Jackson ImmunoResearch).…”
Section: Methodsmentioning
confidence: 99%